Association between Nutritional Status with Severity of Dengue Hemorrhagic Fever in Pediatric Patients - Veronika Lydia Dewi Sugiarto; Komang Trisna Sumadewi; Ni Wayan Rusni Sugiarto (Universitas Muhammadiyah Surabaya, 2026)
Dengue infection remains a major public health concern in tropical regions, including Indonesia, with pediatric patients exhibiting varying degrees of clinical severity. Nutritional status has been suggested as a host-related factor influencing immune response and disease progression. This study aimed to examine the association between nutritional status and dengue severity among pediatric patients treated at Mangusada Regional Hospital in 2024 using the WHO 2009 classification system. A cross-sectional analytic design was applied using secondary data from medical records. Total sampling yielded 120 eligible pediatric dengue patients after exclusion of incomplete records. Nutritional status was assessed using BMI-for-age z-score based on WHO growth standards and categorized into undernutrition, normal nutrition, and overnutrition. Dengue severity was classified as dengue without warning signs and dengue with warning signs/severe dengue for analysis. Statistical analysis was performed using the Chi-square test with Cramér’s V to determine effect size. The results showed that overnutrition was the most frequent nutritional status (55.0%), and dengue with warning signs was the most common severity category (44.2%). Chi-square analysis indicated no statistically significant unadjusted association between nutritional status and dengue severity (χ² = 1.50; p = 0.473), with a small effect size (Cramér’s V = 0.112). These findings should be interpreted cautiously because important potential confounding variables were not included in the analysis.